Human Platelet Antigen-2b Gene Polymorphism in Type 2 Diabetes Mellitus Patients with Macrovascular Complications - Hermawan; Rachmawati Muhiddin; Hasta Handayani Idrus (UMI Medical Journal, 2026)
Background: The prevalence of Type 2 Diabetes Mellitus continues to increase globally, with Indonesia ranking fifth worldwide, affecting an estimated 20.4 million adults as of 2024. Patients with T2DM often experience abnormal platelet activation leading to platelet hyperactivity, which contributes to macrovascular complications such as coronary heart disease, cerebrovascular disease, and peripheral arterial disease. Objective: To analyze the differences in frequency and distribution of HPA gene polymorphisms between T2DM patients with macrovascular complications and those without macrovascular complications. Methods: A case control study was conducted involving 100 T2DM patients, consisting of 50 patients with macrovascular complications and 50 without macrovascular complications. HPA gene polymorphisms were analyzed using the polymerase chain reaction method. Clinical and laboratory variables including age, sex, HbA1c level, hypertension, and dyslipidemia were evaluated. Statistical analyses were performed to determine the association between HPA polymorphisms and macrovascular complications. Results: HPA gene types 1–5 were detected, while HPA-15a and HPA-15b were absent. Most participants were male (53%), aged 18–65 years (84%), had uncontrolled HbA1c levels (93%), were not hypertensive (72%), and had no dyslipidemia (57%). Significant differences were observed in hypertension, dyslipidemia, and HPA-2b polymorphism between the macrovascular and non-macrovascular complication groups (p < 0.05). Multivariate analysis demonstrated that HPA-2b polymorphism was significantly associated with macrovascular complications in patients with Type 2 Diabetes Mellitus (p < 0.001). Conclusion: HPA-2b gene polymorphism is more prevalent in T2DM patients with macrovascular complications and is significantly associated with the occurrence of these complications.